KENYA’S WOMEN LEADING THE WAY: EMPOWERMENT AND INTEGRATION - Mwangi, Benedicta Wanjiku (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
This study examines the imperative role of women in fostering national cohesion, integration, and sustainable peace, particularly in conflict-affected regions like Kenya. National cohesion and integration entail fostering a collective sense of belonging and engagement within a community to collectively address shared challenges and opportunities. The National Cohesion and Integration Commission (NCIC) in Kenya has been established to promote peaceful coexistence among diverse populations. However, the role of women in such processes has often been sidelined, despite their crucial contributions to development and integration. Women’s active involvement in peace negotiations remains limited, although they constitute a significant portion of conflict-affected populations. This paper underscores the necessity of including women in peace processes, emphasizing their capacity to serve as agents of change rather than solely as victims of violence. Traditional narratives portraying women merely as victims inadequately address their multifaceted roles in peacebuilding. Efforts to enhance women’s participation in peace mediation have led to the growth of women mediator networks, bolstering their leadership and coordination abilities. The study also underscores that women’s contributions extend beyond passive roles, with examples of women participating as decision-makers, negotiators, peace activists, and even in military struggles during conflicts. To foster sustainable peace and development, it is imperative to recognize and amplify women’s active involvement in conflict resolution and peacebuilding efforts. This research contributes to the ongoing discourse on women’s agency in peace and security processes and highlights the need to transcend traditional gender stereotypes to ensure holistic and effective peacebuilding.